2017
DOI: 10.1111/lsi.12204
|View full text |Cite
|
Sign up to set email alerts
|

Divided Selves: Professional Role Distancing Among Law Students and New Lawyers in a Period of Market Crisis

Abstract: In the terms of Erving Goffman's classic role‐distancing analysis, newly admitted law students often aspire to an “embraced” lawyer role that directly expresses their personal and political values. Empirical research has suggested that during law school these students are instructed in an amoral and apolitical vision of professionalism. The literature has paid less attention to how students internally experience these norms within their continual processes of self‐construction. This article takes an explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 20 publications
0
20
0
3
Order By: Relevance
“…Instead, many of these respondents suggested that their own emphasis on ethical client service was merely a post hoc rationalization for the decision to "drift" to a corporate law firm instead of starting their careers in public-interest practice settings (Granfield 1992). Thus, one respondent who cited the adversarial professionalism ideal for his decision to work in a large firm (that "everyone deserves a defense, even corporate clients") quickly clarified: "That's probably just a justification for myself so I don't have to feel like a sellout" (Bliss 2018(Bliss , 2020. Pro bono opportunities seemed to alleviate some of this disappointment with the civic significance of working in corporate law.…”
Section: Us Findings: Constrained Divided and Unstable Professionalmentioning
confidence: 99%
“…Instead, many of these respondents suggested that their own emphasis on ethical client service was merely a post hoc rationalization for the decision to "drift" to a corporate law firm instead of starting their careers in public-interest practice settings (Granfield 1992). Thus, one respondent who cited the adversarial professionalism ideal for his decision to work in a large firm (that "everyone deserves a defense, even corporate clients") quickly clarified: "That's probably just a justification for myself so I don't have to feel like a sellout" (Bliss 2018(Bliss , 2020. Pro bono opportunities seemed to alleviate some of this disappointment with the civic significance of working in corporate law.…”
Section: Us Findings: Constrained Divided and Unstable Professionalmentioning
confidence: 99%
“…To understand these layered patterns of assimilation and belonging, we employ the theoretical framework extended by Erving Goffman (1963) and used since by other scholars in theorizing about marginal identities (e.g. Granfield 1991;Yoshino 2007;Bliss 2016). In his work on stigmatized identities, Goffman explains that individuals who possess traits that might differentiate them from mainstream "normals" (1963,5) are likely to employ a range of mechanisms to moderate their visibility (1963,(48)(49)(50)(51).…”
Section: Minority Experiences In Us Jd Programsmentioning
confidence: 99%
“…Americans likewise favor providing opportunity to individuals rather than group-based redistributive results (Kleugel and Smith 1986;Bobo and Kleugel 1993). For lawyers, including judges, socialization into liberal legality in law school and beyond (Schleef 2006;Bliss 2017) exacerbates these cognitive and normative tendencies. 4 Deference to managerialization of Title VII likewise reflects capitalism's market ideals, especially that of managerial and business prerogative.…”
Section: Can Managerialization and Legal Endogeneity Be Curtailed?mentioning
confidence: 99%
“…4. Law students also have available to them and may adopt notions of substantive justice, but liberal legality typically dominates law school socialization (Scheingold and Sarat 2014;Bliss 2017). opposition to aggressive regulatory enforcement of many types, from labor to environmental protection to occupational safety and health law (Stryker 1996).…”
Section: Can Managerialization and Legal Endogeneity Be Curtailed?mentioning
confidence: 99%